Letter from Edward N. Kent to James Curtis Booth, November 21, 1855 - Kent, Edward (1855)
Edward N. Kent of the United States Assay Office at New York writes to inform James Curtis Booth (1810-1888) that he prefers to use hard-wood charcoal from New York rather than depend upon supplies from Philadelphia.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City